(3WQb heTGcd GdeMGSHI Yf GdfeGPL hGdTQcGJ (B:s (3OQGSI YdejI dCMOK GdEJLGgGJ GdJj JXefJgG eYGjjQ GdeMGSHI aj eUQ hGdOhd GdeJbOeI heYGjjQ GdeMGSHI GdOhdjI (B/s - (3ZGdj, LhQL OGfjGds ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2002)
(3ENJjGQ WQjbI GdeMGSHI Yf GdEfOeGL(B-(3GdeTGcd GdeMGSHjI GdeQJHWI HGdJbjje(B-(3GdeMGSHI Yf GdEfOeGL aj LeghQjI eUQ GdYQHjIs
Keywords: (3eMGSHIs; (3eMGSHI GdTQcGJs; (3eUQ(B- (3eMGSHIs